Herpes simplex virus infection and risk of atrial fibrillation: a nationwide study - Chiang, Chia-Hung; Huang, Chin-Chou; Chan, Wan-Leong; Huang, Po-Hsun; Chen, Yu-Chun; Chen, Tzeng-Ji; Lin, Shing-Jong; Chen, Jaw-Wen; Leu, Hsin-Bang (International journal of cardiology, 2013)
Background - Currently, precise mechanisms of atrial fibrillation (AF) are uncertain but proved to be associated with inflammation. There has been no specific study to evaluate the risk of AF after diagnosis of herpes simplex virus (HSV) infection. - Methods - To investigate the relationship between HSV infection and the occurrence of AF, we used a nation-wide population-based dataset from Taiwan. A total of 15,180 patients with diagnosis of HSV infection were included in the study group from a 1,000,000 sampling cohort dataset between January 2000 and December 2003. Another 73,197 age-, gender-, and comorbidity-matched subjects without HSV infection were included in the control group. The log-rank test was performed to analyze the differences in accumulated AF-free survival rates between these 2 groups. Cox proportional hazard regressions were performed to evaluate the independent factor in determining the longitudinal hazard of AF. - Results - During a 3-year follow-up period, 240 patients from the study group (1.6%) and 801 patients from the comparison group (1.1%) had newly developed AF. The log-rank test showed that patients with HSV had significantly higher incidence of AF development than those without HSV (p<0.001). After Cox model adjustment for risk factors and comorbidities, HSV infection was independently associated with increased risk of AF development (hazard ratios [HR], 1.39; 95% confidence interval [CI], 1.2-1.60; p<0.0001). - Conclusion - Our study concludes that HSV infection may be independently associated with an increased risk of future AF development.
Available online: 22 July 2011
Gesehen am 14.04.2021